2012
DOI: 10.1586/eci.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune heart disease: role of sex hormones and autoantibodies in disease pathogenesis

Abstract: Cardiovascular disease (CVD) and autoimmune diseases (ADs) are the first and third highest causes of death in the USA, respectively. Men have an increased incidence of the majority of CVDs, including atherosclerosis, myocarditis, dilated cardiomyopathy and heart failure. By contrast, nearly 80% of all ADs occur in women. However, in one category of ADs, rheumatic diseases, CVD is the main cause of death. Factors that link rheumatic ADs to CVD are inflammation and the presence of autoantibodies. In this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 191 publications
0
78
0
Order By: Relevance
“…Indeed, men develop atherosclerotic plaques earlier and more extensively than women, while the number of cardiovascular events in women increases strikingly with menopause, suggesting that sex hormones influence heart disease. 58,59,63 …”
Section: Sex Differences In Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, men develop atherosclerotic plaques earlier and more extensively than women, while the number of cardiovascular events in women increases strikingly with menopause, suggesting that sex hormones influence heart disease. 58,59,63 …”
Section: Sex Differences In Pathophysiologymentioning
confidence: 99%
“…Heart failure can be the consequence of a number of inflammatory cardiovascular conditions including atherosclerosis, myocarditis, DCM and PPCM. 63,64 Sheppard et al . found that men with myocarditis or acute DCM had higher cardiac expression of proteins associated with apoptosis, such as Fas and tumor necrosis factor receptor 1, than women, while patients with the highest levels of these apoptosis markers had minimal improvement in LVEF.…”
Section: Sex Differences In Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…41 It is known that sex difference plays an important role in the immunopathogenesis of cardiovascular and autoimmune disease. 42 The findings of our study should be interpreted in this context, and further studies that investigate the possible influence of sex difference on the T H 17/T reg ratio in RHD are needed.…”
Section: Discussionmentioning
confidence: 83%